The effects of incivility on learning burnout in Chinese nursing interns: mediating roles of career calling and self-efficacy - Na, Ou; Sanyang, Qi; Pengxin, Li; Jimei, Hu; Minmin, Hu (Frontiers in Psychology, 2025)
IntroductionIncivility in clinical nursing education (ICNE) is a pervasive issue globally, adversely affecting nursing interns’ psychological well-being and professional development. However, the mediating mechanisms linking ICNE to learning burnout remain underexplored, particularly in non-Western contexts. This study investigates the impact of incivility in clinical nursing education on learning burnout among Chinese nursing interns and examines the mediating roles of career calling and self-efficacy.MethodsUsing a sample of 250 nursing interns from a tertiary hospital in Hunan Province, China, data were collected through validated questionnaires. Statistical analyses, including regression and structural equation modeling, were conducted to explore relationships among variables.ResultsIncivility significantly increased learning burnout levels (β = 0.784, p < 0.001), explaining 78.6% of the variance. Career calling and self-efficacy were found to mediate this relationship, accounting for 27.3 and 20.6% of the indirect effects, respectively. The total indirect effect was 47.9%, while the direct effect was 52.1%.ConclusionIncivility in clinical nursing education significantly contributes to learning burnout. Career calling and self-efficacy partially mediate this effect, suggesting that enhancing these factors may mitigate the negative impact of incivility. These findings highlight the importance of improving the educational environment and providing personalized support to nursing interns.